Evaluation of InSAR monitoring data for post‐tunnelling settlement damage assessment - Giardina, Giorgia; Milillo, Pietro; DeJong, Matthew J.; Perissin, Daniele; Milillo, Giovanni (Structural control and health monitoring, 2019)
Summary The increasing demand for underground infrastructure should be supported by innovation in monitoring and damage assessment solutions to minimise damage to surface structures caused by ground settlements. This paper evaluates the use of multitemporal synthetic aperture radar interferometry (MT‐InSAR) to calculate tunnelling‐induced deformations of buildings. The paper introduces a step‐by‐step procedure to use InSAR displacements as an input to the structural damage assessment. After a comparison between traditional and InSAR monitoring data for the London area during the Crossrail excavation, the high resolution, high density InSAR‐based displacements were used to evaluate the building deformations for a number of case studies. Results demonstrate the quality of information provided by InSAR data on soil‐structure interaction mechanisms. Such information, essential to evaluate current damage assessment procedures, is typically only collected for relatively few buildings due to the cost of traditional monitoring. A comparison between damage indicators derived from greenfield assumptions and building displacements quantifies the practical benefit of the proposed step‐by‐step procedure. This work aims at filling the gap between the most recent advances in remote sensing and the civil engineering practice, defining the first step of an automated damage assessment procedure which can impact large scale underground projects in urban areas.